2002
DOI: 10.1074/jbc.m111573200
|View full text |Cite
|
Sign up to set email alerts
|

The DNA Polymerase Domain of polε Is Required for Rapid, Efficient, and Highly Accurate Chromosomal DNA Replication, Telomere Length Maintenance, and Normal Cell Senescence inSaccharomyces cerevisiae

Abstract: Saccharomyces cerevisiae POL2 encodes the catalytic subunit of DNA polymerase ⑀. This study investigates the cellular functions performed by the polymerase domain of Pol2p and its role in DNA metabolism. The pol2-16 mutation has a deletion in the catalytic domain of DNA polymerase ⑀ that eliminates its polymerase and exonuclease activities. It is a viable mutant, which displays temperature sensitivity for growth and a defect in elongation step of chromosomal DNA replication even at permissive temperatures. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
92
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(103 citation statements)
references
References 64 publications
10
92
1
Order By: Relevance
“…Between 15 and 20 discrete foci were detected that were Origin Recognition Complex (ORC), S phase-, and origin-specific (Pasero et al 1997). The same type of foci were later observed by visualizing replisome components such as PCNA and DNA polymerase a or e by immunostaining or fluorescent tagging in living cells (Ohya et al 2002;Hiraga et al 2005;Kitamura et al 2006). Because the number of these foci is far smaller than the number of replication forks, they are thought to correspond to replication factories in which several elongating forks are grouped.…”
Section: Dna-based Compartmentsmentioning
confidence: 80%
“…Between 15 and 20 discrete foci were detected that were Origin Recognition Complex (ORC), S phase-, and origin-specific (Pasero et al 1997). The same type of foci were later observed by visualizing replisome components such as PCNA and DNA polymerase a or e by immunostaining or fluorescent tagging in living cells (Ohya et al 2002;Hiraga et al 2005;Kitamura et al 2006). Because the number of these foci is far smaller than the number of replication forks, they are thought to correspond to replication factories in which several elongating forks are grouped.…”
Section: Dna-based Compartmentsmentioning
confidence: 80%
“…The connection between dysfunctional DNA replication and genome instability has been firmly established in yeast by the elevated rates of many types of mutagenic and clastogenic events observed in a variety of DNA replication mutants (Aguilera and Klein 1988;Gordenin et al 1992;Ruskin and Fink 1993;Reagan et al 1995;Ohya et al 2002;Meyer and Bailis 2007). In particular, mutations that disrupt the polymerase function of Pol d confer increased rates of mutation and recombination (Gordenin et al 1992;Tran et al 1995Tran et al , 1996Tran et al , 1997Kokoska et al 1998Kokoska et al , 2000Lobachev et al 1998Lobachev et al , 2000Galli et al 2003), consistent with incom- 18.8 (9.3-24.1) 4.2 9.6 (6.7-11.4) 5.7 pol3-t rev7D…”
Section: Discussionmentioning
confidence: 99%
“…The POL2 gene of Pol e consists of two halves: the N-half encodes the active polymerase and the C-half comprises an inactive polymerase (30). The C-half of POL2 is essential to cell viability and binds the accessory factors Dpb2, -3, and -4, whereas the active N-terminal polymerase encoded by POL2 is not essential, although cells are severely compromised in S-phase progression (31)(32)(33). Our earlier chemical cross-linking MS study showed that the N-and C-halves of Pol2 each have numerous internal cross-links, yet there is only one cross-link between the two halves of Pol2, suggesting the N-and C-halves of Pol2 are distinct folding units connected by a linker region that separates them spatially (SI Appendix, Fig.…”
Section: Implications Of N-tier Ahead Of C-tier During Cmg Translocatmentioning
confidence: 99%